Feasibility of Integrating Self-regulated Learning in Physics-STEM Module to Train Creative Thinking Skills - Wahyuni, Sri; Suwarma, Irma Rahma; Hasanah, Lilik (KnE Social Sciences, 2024)
The teaching materials are the most important components to achieve the learning objectives for teaching and learning. A module is one of the teaching materials that is systematically designed based on curriculum and packaged into learning units, so that it can be used independently by students to achieve learning objectives. Learning objectives are oriented to 21st century skills, one of them being creative thinking skills that can be trained through STEM approach’. On the other hand, implementing STEM learning in Islamic boarding schools requires self-regulated learning. This is intended to foster student independence in order to have optimal learning achievement both academically and tahfidz. Considering that learning in Islamic boarding schools has a solid routine and demands more learning outcomes; therefore, researchers are interested in conducting research on the development of integrating self-regulated learning on physics-STEM modules to train creative thinking skills. This study uses a mixed method with a sequential exploratory design. It is intended to obtain qualitative and quantitative data. Qualitative data is needed to design self-regulated learning on physics-STEM module. Quantitative data is used to determine the validity of the module’s feasibility and improvement of creative thinking skills. However, this study only arrived at the feasibility of integrating self-regulated in physics-STEM module, so it emphasizes more on qualitative data. The creative thinking skill instrument was designed based on the 2021 PISA framework. The participants in this study were three lecturers of expert validators. The results showed that the validation of self-regulated learning in physics-STEM module is of very high category. Keywords: self-regulated learning, physics-STEM module, creative thinking skills